(untitled) (Circe de clásicos y modernos, 2018)
The paper analyzes the character of Aseneth, main character of the Hellenistic Jewish novel Joseph and Aseneth according to his decision of leaving his former life to adopt the monotheistic belief. From this point we will meditate on identity and the phenomenon of the proselyte, its ‘acceptance’ inside the Jewish community and outside it, so we will use some of the historical and literary sources that testify the existence of proselyte and its insertion into a society in a time of transition between the pagan and the Christian world.